Apolipoprotein E ε4/4 genotype limits response to dietary induction of hyperhomocysteinemia and resulting inflammatory signaling. Issue 5 (May 2022) - Seaks, Charles E; Weekman, Erica M; Sudduth, Tiffany L; Xie, Kevin; Wasek, Brandi; Fardo, David W; Johnson, Lance A; Bottiglieri, Teodoro; Wilcock, Donna M
Vascular contributions to cognitive impairment and dementia (VCID) are the second leading cause of dementia behind Alzheimer's disease. Apolipoprotein E (ApoE) is a lipid transporting lipoprotein found within the brain and periphery. The APOE ε4 allele is the strongest genetic risk factor for late onset Alzheimer's disease and is a risk factor for VCID. Our lab has previously utilized a dietary model of hyperhomocysteinemia (HHcy) to induce VCID pathology and cognitive deficits in mice. This diet induces perivascular inflammation through cumulative oxidative damage leading to glial mediated inflammation and blood brain barrier breakdown. Here, we examine the impact of ApoE ε4 compared to ε3 alleles on the progression of VCID pathology and inflammation in our dietary model of HHcy. We report a significant resistance to HHcy induction in ε4 mice, accompanied by a number of related differences related to homocysteine (Hcy) metabolism and methylation cycle, or 1-C, metabolites. There were also significant differences in inflammatory profiles between ε3 and ε4 mice, as well as significant reduction in Serpina3n, a serine protease inhibitor associated with ApoE ε4, expression in ε4 HHcy mice relative to ε4 controls. Finally, we find evidence of pervasive sex differences within both genotypes in response to HHcy induction.